PROBLEMA TRAUMATIK: KEKERASAN SEKSUAL PADA REMAJA - Purbararas, Esmu Diah (IJTIMAIYA: Journal of Social Science and Teaching, 2018)
The purpose of this study is to find out how the experience of a teenager who experienced sexual violence and any traumatic problems experienced by adolescents who experienced sexual violence. Subjects in this study were female adolescents, who focused on adolescents who had experienced acts of sexual violence named FN, the subject here is a friend of researchers and data sources taken directly and indirectly using electronic media in the form of BBM (BlackBerry Messenger). Researchers use a phenomenological paradigm in which the focus of the researcher is the primary target is the meaning of the experiences, events, status held by the participants related to the violence experienced. From the results of research conducted by researchers by interviewing the victim, the victim tells that the main motive that the victim is doing is by coercion and threat, so victim does not want to do that, because victim feel afraid and cannot take action again. From the acts of violence experienced by the victim we can see the consequences caused by the violence the victim suffered trauma that is very heavy that is: (1) do not believe in men, (2) become a woman naughty or woman that can be paid, (3) become (4) getting drunk and bruised as outlet, and (5) being a lesbian because of his trauma and not believing in a man. By experiencing the incident the victim also requires treatment so that the trauma experienced will gradually improve. Keywords: Sexual Violence, Traumatic Problems, Psychological Impact